ChemInform Abstract: SnO Nanoparticles as an Efficient Catalyst for the One‐Pot Synthesis of Chromeno[2, 3‐b]pyridines and 2‐Amino‐3, 5‐dicyano‐6‐sulfanyl Pyridines. Issue 15 (April 2015) - Safaei‐Ghomi, Javad; Shahbazi‐Alavi, Hossein; Heidari‐Baghbahadorani, Elham
Abstract: The catalyst is recycled and reused for five times without significant loss of activity.